Konfigurasi Jaringan Mikrotik dengan Metode Wireless Distribution System Pada Institut Teknologi dan Bisnis Indonesia (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2022)
Wireless Distribution System is a wireless network expansion system, where with the Wireless Distribution System, it allows us to build wireless infrastructure without having to build a network cable backbone as an interconnection between bridges, where it is not possible to install a wired network, because it is more expensive, limited. , or it is physically impossible to create a wired network.Wireless Distribution System can be used in two types of connectivity modes between Access points. Wireless Bridging where the access points of the Wireless Distribution System only communicate with each other between APs and do not allow other wireless clients or stations to access them. Wireless repeater where access points communicate with each other and also with wireless stations .